A Novel Assessment of Braking Reaction Time following THA Using a New Fully Interactive Driving Simulator. Issue 2 (July 2015) - Ruel, Allison V.; Lee, Yuo-yu; Boles, John; Boettner, Friedrich; Su, Edwin; Westrich, Geoffrey H.
Background: After total hip replacement surgery, patients are eager to resume the activities of daily life, particularly driving. Most surgeons recommend waiting 6 weeks after surgery to resume driving; however, there is no evidence to indicate that patients cannot resume driving earlier. Questions/Purposes: Our purpose was to evaluate when in the recovery period following THA that patients regain or improve upon their preoperative braking reaction time, allowing them to safely resume driving. Methods: We measured and compared pre- and postoperative braking reaction times of 90 patients from 3 different surgeons using a Fully Interactive Driving Simulator (Simulator Systems International, Tulsa, OK). We defined a return to safe braking reaction time as a return to a time value that is either equal to or less than the preoperative braking reaction time. Results: Patients tested at 2 and 3 weeks after surgery had slower braking reaction times than preoperative times by an average of 0.069 and 0.009 s, respectively. At 4 weeks after surgery, however, patients improved their reaction times by 0.035 s ( p = 0.0398). In addition, at 2, 3, and 4 weeks postoperatively, the results also demonstrated that patient less than 70 years of age recovered faster. Conclusions: Based upon the results of this study, most patients should be allowed to return to driving 4 weeks following minimally invasive primary total hip arthroplasty.